Developing an Inclusive Learning Environment for Refugee Students in Higher Education - Patricia J Higgins; Mitsunori Misawa (Adult Education Research Conference, 2019)
The purpose of this session is to facilitate a dialogue focused on creating an inclusive learning environment for a marginalized population of adult learners, refugee students in higher education.
Keywords: Adult Learners; Refugees; Inclusive Learning Environments